Strengthening Cybersecurity of The United Arab Emirates After The Establishment of diplomatic Relations With Israel - Utami, Afini Nurdina; Basyar, M. Hamdan (Journal Of Middle East and Islamic Studies, 2022)
The United Arab Emirates established diplomatic relations with Israel in September 2020. This decision is in line with the United Arab Emirates' national commitment to enhance the development of the country's potential. The two countries agreed to enhance cooperation in the fields of cyber and technology. The regional threat posed by Iran is one of the factors driving cooperation between the two countries in the field of cybersecurity. This study aims to answer the background of the two countries’ increasing cooperation in the field of cybersecurity and how to strengthen cybersecurity as one of the objectives of cooperation after the inauguration of diplomatic relations between the two countries. This research uses a descriptive qualitative method through literature review method. The study concluded that the strengthening of cybersecurity between the United Arab Emirates and Israel increased significantly after normalization with various activities and agreements such as the holding of Cyber-tech Global Dubai, joint training in the field of cybersecurity, and the construction of the first UAE-Israel startup company that puts the cybersecurity theme forward.